Management of Tonsillar Lipoma: Is Tonsillectomy Essential?. (4th February 2014) - Kanotra, Sohit P.; Davies, Joel
Abstract : Tonsillar lipomas are rare benign tumors, with only a limited number of cases reported in the literature. Excision of the lipoma along with tonsillectomy has been proposed as the usual treatment option. We report a case of tonsillar lipoma which was managed by excision of the lesion without the need for a tonsillectomy. No recurrence was reported at a 2-year followup. A worldwide literature review was done to better define the clinical and histopathological features of these lesions. The authors propose that routine tonsillectomy is not required for these benign lesions and that simple excision of the stalk of the lipoma is sufficient.